PENGEMBANGAN BAHAN AJAR BERBASIS ETNOMATEMATIKA PADA MATERI BANGUN DATAR DI SD/MI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools is often considered difficult due to its abstract nature and the limited availability of contextual teaching materials. This condition causes students to have low understanding, especially in plane geometry topics. This study aims to develop ethnomathematics-based teaching materials by integrating Acehnese local culture such as traditional houses, songket cloth, and Gayo carvings. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were two media experts, two material experts, two language experts, two teachers, and 15 fourth-grade students of MIN 10 Aceh Besar. Data were collected through validation sheets and response questionnaires, then analyzed using descriptive qualitative and quantitative techniques. The results showed that the developed teaching materials were categorized as very feasible based on expert validation, with percentages of 94.64% from media experts, 85.41% from material experts, and 79.54% from language experts. In addition, the practicality test showed very positive responses from teachers (97.22%) and students (97.33%). Therefore, ethnomathematics-based teaching materials are considered very feasible and practical to be used as supporting learning resources in elementary mathematics, particularly in plane geometry learning.